Assessment of upper body muscle activity during salat and stretching exercise : a pilot study. - Ibrahim, Fatimah; Ahmad, Siti Anom (2012)
Salat is the practice of formal prayer for Muslims. It involves with both spiritual and physical acts. This paper presents electromyography (EMG) output during the “takbeeratul-ihram (TI)”, one of the postures in Salat and stretching exercise. Comparisons on EMG outputs between TI and stretching exercise are discussed. Ten healthy participants (five males and five females) were recruited for the investigation. The EMG signals were recorded from back scapula, upper trapezius, biceps brachii and pectoralis major muscles. The results showed that higher EMG signals in pectoralis major and biceps during performing the stretching posture. However, for TI posture, the EMG activities are higher in back scapula and upper trapezius muscles.